Perancangan Web Sebagai Media Promosi Koleksi Naskah Kuno Minangkabau di Museum Adityawarman Sumatera Barat - Jayanti, Susan; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
The purpose of this study is to describe design web as pomotion media collection of naskah kuno Minangkabau at Museum Adityawarman West Sumatera, so that can to acces by users according to online. The Data of this study is colletion of naskah kuno Minangkabau at Museum Adityawarman West Sumatera. Data were collected by using observation and record with staff at Museum Adityawarman West Sumatera. Design web using Adobe Dreamweaver CS5. The findings of the study showed that promotion activity collection of naskah kuno at Museum Adityawarman West Sumatera to worked with socialization method, competition, parade, and to prepare information about cultural tour of Museum Adityawarman on the web Province West Sumatera. Media of promotion in Museum Adityawarman West Sumatera is baliho, brochure and poster. Keywords: promotion; web design; manuscript; Museum Adityawarman